2010
DOI: 10.1161/hypertensionaha.110.153536
|View full text |Cite|
|
Sign up to set email alerts
|

Inorganic Nitrate Supplementation Lowers Blood Pressure in Humans

Abstract: Abstract-Ingestion of dietary (inorganic) nitrate elevates circulating and tissue levels of nitrite via bioconversion in the entero-salivary circulation. In addition, nitrite is a potent vasodilator in humans, an effect thought to underlie the blood pressure-lowering effects of dietary nitrate (in the form of beetroot juice) ingestion. Whether inorganic nitrate underlies these effects and whether the effects of either naturally occurring dietary nitrate or inorganic nitrate supplementation are dose dependent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
508
10
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 538 publications
(569 citation statements)
references
References 40 publications
39
508
10
12
Order By: Relevance
“…With a burgeoning awareness of the potential importance of NO 3 -in sport and exercise, an ever-increasing variety of NO 3 -fortified products are becoming commercialised, ranging from sport bars and lozenges to BR capsules. Importantly, NO 3 -salts (in solution or via capsule) are readily available for both oral and intravenous administration and ] ratio, as defined in Table 1) was relatively consistent (1.0-1.2) and is in keeping with the work of most using BR [11][12][13][14], but inconsistent with Webb et al hrs, and a plasma t½ of >6 hrs is found irrespective of KNO 3 dose (4 -24 mmol).…”
Section: Nitrate (No 3 -) Sourcementioning
confidence: 70%
See 2 more Smart Citations
“…With a burgeoning awareness of the potential importance of NO 3 -in sport and exercise, an ever-increasing variety of NO 3 -fortified products are becoming commercialised, ranging from sport bars and lozenges to BR capsules. Importantly, NO 3 -salts (in solution or via capsule) are readily available for both oral and intravenous administration and ] ratio, as defined in Table 1) was relatively consistent (1.0-1.2) and is in keeping with the work of most using BR [11][12][13][14], but inconsistent with Webb et al hrs, and a plasma t½ of >6 hrs is found irrespective of KNO 3 dose (4 -24 mmol).…”
Section: Nitrate (No 3 -) Sourcementioning
confidence: 70%
“…In addition, taken together there is good evidence that time to peak NO 3 -may depend on the source of NO 3 -, although there are notable exceptions [11]. In general, a KNO 3 solution/capsule and NO 3 -containing gel (SiS Go+Nitrate) appear to exhibit an earlier peak (~1hr) when compared with BR at a similar loading dose.…”
Section: Nitrate (No 3 -) Sourcementioning
confidence: 94%
See 1 more Smart Citation
“…In contrast, where large falls in systolic pressure have been reported, the groups studied have been much younger. The subjects in Webb et al's study 26 were 25.5 ± 4.5 years old; the subjects in Kapil et al's study 27 were 22.5 ± 0.9 years old.…”
Section: Discussionmentioning
confidence: 91%
“…[22][23][24] It has previously been shown that dietary nitrate supplementation, via sequential reduction of nitrate to nitrite and nitric oxide, can lower blood pressure and improve endothelial function in healthy humans. [25][26][27][28][29] Inorganic nitrate from the diet may have numerous other beneficial effects including improving exercise tolerance, ameliorating ischaemia-reperfusion injury, inhibition of platelet aggregation, protection against gastrointestinal infection, and protection against gastric ulceration (for review see 30 ). Furthermore, Lundberg and Weitzberg's group has shown that, in endothelial nitric oxide synthase (eNOS) knockout mice, supplementation of the diet with inorganic nitrate improved glucose tolerance and ameliorated other features of the metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%